PENGADOPSIAN MEDIASI SEBAGAI ALTERNATIF PENYELESAIAN SENGKETA DALAM RANAH PENYELESAIAN KONFLIK HUKUM ADAT DI BALI - I Gusti Ayu Stefani Ratna Maharani (Jurnal Hukum Lex Generalis, 2024)
The purpose of this study is to further examine the adoption of mediation as an alternative non-litigation dispute resolution in the realm of conflict resolution or customary law disputes in Bali. This study uses a normative legal research method with a statutory and comparative approach. From the results of the studies conducted, it can be seen that there is an adoption of mediation as an alternative means of dispute resolution in the realm of customary law conflict resolution in Bali which is based on Law Number 30 of 1999 concerning Arbitration and Alternative Dispute Resolution outside the Court (Non-Litigation), besides that it is also based on the Regulation of the Supreme Court No. 2 of 2016 concerning Mediation Procedure in Court which is an amendment to PERMA No. 1 of 2008. In the realm of customary law, there are often conflicts or disputes involving indigenous peoples such as conflicts regarding the issue of fatherhood in traditional villages, village membership, regarding the seizure of village land, and separation from membership of the traditional banjar and of course there are still many problems that occur in the community. The scope of the customary law community, which if resolved through the courts (litigation) will certainly take a lot of time and cost a lot of money. Therefore, it is necessary to adopt mediation as an alternative dispute resolution into a pattern of conflict resolution involving customary law communities regarding customary disputes in the customary village area which will certainly be more efficient, cost-effective and does not take a long time.